Does halo effect of innovative firms moderate the impact of working capital efficiency on firm value? Evidence from India - Sayantan Kundu (Cogent Economics & Finance, 2022)
The purpose of this study is to examine whether perceived innovativeness moderates the relationship between working capital management (WCM) and firm value. The study uses a sample of 200 listed Indian firms for 2015–2019. The firms are classified into innovative and non-innovative categories using the OECD and the EU Industrial R&D Investment Scoreboard 2018. Using OLS and GMM-DPD estimations, the study finds in accordance with the prior literature that a sample of firms exhibits a positive relationship between WCM efficiency and firm value. The original contribution of the paper is finding that low R&D and high R&D firms are treated differently when investors factor WCM into prices. The firms belonging to industries that are perceived to be innovative are not penalised in terms of valuation even if they follow inefficient WCM. However, firms that belong to industry sectors that are perceived to be non-innovative experience a drop in their valuation if their WCM is inefficient. The authors argue that this difference is due to the halo effect of innovative firms. The results imply that the halo effect obscures the true valuation. Hence, investors should learn to avoid valuing innovative firms’ WCM based merely on their classification into an innovative industry sector.